2004
DOI: 10.1523/jneurosci.4868-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role For Serum Response Factor in Neuronal Survival

Abstract: Recent studies indicate that neuroprotection afforded by brain-derived neurotrophic factor (BDNF) is mediated by extracellular signalregulated kinase (ERK) and phosphatidylinositol-3 kinase (PI3K). However, the mechanisms by which ERK and PI3K exert neuroprotection are not completely understood. Because ERK1/2 and PI3K both stimulate serum response element (SRE)-mediated gene expression, and serum response factor (SRF) is indispensable for SRE-mediated transcription, we investigated whether SRF contributes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 64 publications
3
54
1
Order By: Relevance
“…In addition to ERK1/2, SRF activity may be regulated by PI3K. PI3K contributed to TCF-independent activation of SRF in NGFstimulated PC12 cells and BDNF activation of an SRE reporter in cultured cortical neurons (Poser et al, 2000;Chang et al, 2004). In our hands, PI3K was neither required nor sufficient to activate MKL1/SRF-driven transcription.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In addition to ERK1/2, SRF activity may be regulated by PI3K. PI3K contributed to TCF-independent activation of SRF in NGFstimulated PC12 cells and BDNF activation of an SRE reporter in cultured cortical neurons (Poser et al, 2000;Chang et al, 2004). In our hands, PI3K was neither required nor sufficient to activate MKL1/SRF-driven transcription.…”
Section: Discussionmentioning
confidence: 51%
“…SRF regulation by ERK1/2 is well established (for review, see Shaw and Saxton, 2003) and was demonstrated in cultured primary neurons responding to BDNF (Chang et al, 2004). The major mechanism mediating that effect has been proposed to rely on ERK1/ 2-mediated phosphorylation of the p62TCF/Elk-1 (Shaw and Saxton, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…bFGF induced phosphorylation and activation of ERK1/2 and PI3-kinase signaling pathways. Both ERK1/2 and PI3-kinase signaling pathways have been implicated in protecting various types of neurons against different injuries (Xia et al, 1995;Dudek et al, 1997;Hetman et al, 1999;Hetman and Xia, 2000;Chang et al, 2004). However, their involvement in neuroprotection in Parkinson's disease models is essentially uncharacterized, although recent reports implicated them in GDNF or NGF protection against 6-OHDA ( Salinas et al, 2003;Ugarte et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Both ERK1/2 and PI3-kinase pathways are crucial for bFGF protection against rotenone bFGF can activate several signal transduction pathways that have been implicated in neuroprotection against different forms of cellular insult (Hetman et al, 1999;Desire et al, 2000;Pardo et al, 2002;Chang et al, 2004). To investigate the underlying mechanisms responsible for bFGF protection against rotenone, SH-SY5Y cells were stimulated with bFGF for 0 -30 min and analyzed for activation of ERK1/2 and PI3-kinase pathways by Western blot analysis.…”
Section: Growth Factor Protection Of Sh-sy5y Cells Against Rotenone-imentioning
confidence: 99%
“…Accordingly, the Ras/MAPK and the PI3-K pathways are known to stimulate the serum response factor (SRF), which plays a role in neuronal survival. 77 Neurotrophins activate other transcription factors, which can also upregulate the expression of several target genes. Akt was also shown to inhhibit Forkhead transcription factors, inhibiting their ability to induce the expression of death genes.…”
mentioning
confidence: 99%